Medium pressure hydrate based gas separation (HBGS) process for pre-combustion capture of carbon dioxide employing a novel fixed bed reactor - Babu, Ponnivalavan; Kumar, Rajnish; Linga, Praveen (International Journal of Greenhouse Gas Control, 2013)
This work presents an effective medium pressure hydrate based gas separation (HBGS) process for pre-combustion carbon dioxide capture in a novel fixed bed column. 2.5 mol% propane was added to the fuel gas mixture as an additive to decrease the operating pressure of the HBGS process. Hydrate formation kinetics was investigated at three different pressures (4.5, 5.5 and 6.0 MPa respectively) and at 274.15 K. The performance of silica sand and silica gel as a medium was evaluated. In silica sand bed, multiple nucleation events were observed. In silica gel bed, the gas uptake and water conversion to hydrates was significantly low at any given driving force than that obtained in silica sand bed. Experiments at different water saturation levels (50, 75 and 100%) in silica sand bed were investigated at 6.0 MPa and 274.15 K. It was found that at 50% water saturation, gas consumed for hydrate formation and water conversion to hydrates was almost three times that at 100% saturation. Water to hydrate conversions of up to 64.3% was achieved after 4 h of hydrate formation for the 50% water saturated silica sand bed. Our study presents an opportunity to scale up the HBGS process for CO2 capture with enhanced kinetics by employing a fixed bed reactor configuration. Decomposition experiments at a driving force of Delta T of 10 K and 23K were carried out to recover the gas consumed for hydrate formation and it was found that Delta T of 23 K was sufficient to recover the hydrated gas. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Gas hydrates; Global warming; Pre-combustion; Separation

Morphology of carbon dioxide-hydrogen-cyclopentane hydrates with or without sodium dodecyl sulfate - Lim, Yu-An; Babu, Ponnivalavan; Kumar, Rajnish; Linga, Praveen (Crystal Growth & Design, 2013)
In this study, effects of cyclopentane (CP) and sodium dodecyl sulfate (SDS) on the hydrate formation morphology were investigated. A gas mixture of 40.0 mol % carbon dioxide and 60.0 mol % hydrogen was used in an unstirred system with subcooling as the driving force. Experimental pressure is at 6.0 MPa and experimental temperatures used are at 275.65 and 277.65 K (Delta T = 15.15 and 13.15 K). Formation of hydrates started at the cyclopentane-liquid water interface. Cloud-like, equiaxed skewed dendritic, equiaxed orthogonal dendritic, long dendritic, and cactus-like crystals could be observed for the experiments in the absence of surfactants. Rapid hydrate formation was observed for the experiments with 0.9 mL CP with or without the presence of surfactants compared to the experiments with 0.45 mL CP system at the same experimental conditions. The addition of SDS had led to a change in the hydrate crystal morphology, forming fiber-like crystals from the hydrate layer. Hydrates had also shown affinity to metal surfaces and tend to grow rapidly because of better heat transfer capacity. Gas uptake measurements were found to correlate well with the morphological observations. On the basis of the morphological observations, the mechanism of the CO2-H-2-CP system in an unstirred system is presented.